Should Ultrasonographic Giant-Cell Arteritis Signs be Detected in Patients with Polymyalgia Rheumatica? - Fazıl Kulaklı; İlker Fatih Sari; Erdem Çaylı; Nurçe Çilesizoğlu Yavuz (Medical Laboratory Technology Journal, 2021)
Based on the presence of ultrasonographic findings of Giant-Cell Arteritis in Polymyalgia Rheumatica patients using Ultrasonography on the temporal artery, the study contributes to the literature evaluating the unclear relationship between Polymyalgia Rheumatica and Giant-Cell Arteritis. It raises awareness that Ultrasonography can be used instead of biopsy in patients with suspected Giant-Cell Arteritis. Twenty patients were newly diagnosed with Polymyalgia Rheumatica and included 20 participants as a control group in the study. The Polymyalgia Rheumatica group was evaluated at baseline and sixth month, while the control group was only assessed at baseline. Laboratory, clinical, and ultrasonographic findings of all participants were assessed. Gray-scale Ultrasonography and colored Doppler Ultrasonography were used to present halo and compression, occlusion, and stenosis in addition to intima-media complex thickness in bilateral temporal arteries and frontal-parietal branches by an experienced radiologist blinded to the subject. No significant difference was found between Polymyalgia Rheumatica and control groups based on demographic features, clinical and ultrasonographic results at baseline and sixth month. Erythrocyte sedimentation rate of Polymyalgia Rheumatica at baseline was statistically higher than the control group. Erythrocyte sedimentation rate values have declined significantly in Polymyalgia Rheumatica patients, but no significant changes were found for clinical or ultrasonographic features during the sixth month. Ultrasonographic findings of Giant-Cell Arteritis are not present in newly diagnosed and six months followed up Polymyalgia Rheumatica patients. Further studies are needed.